Disruptions of the intestinal microbiome in necrotizing enterocolitis, short bowel syndrome, and Hirschsprung’s associated enterocolitis - Till, Holger; Castellani, Christoph; Moissl-Eichinger, Christine; Gorkiewicz, Gregor; Singer, Georg (Frontiers in Microbiology, 2015)
Next generation sequencing techniques are currently revealing novel insight into the microbiome of the human gut. This new area of research seems especially relevant for neonatal diseases, because the development of the intestinal microbiome already starts in the perinatal period and preterm infants with a still immature gut associated immune system may be harmed by a dysproportional microbial colonization. For most gastrointestinal diseases requiring paediatric surgery there is very limited information about the role of the intestinal microbiome. This reviews aims to summarize the current knowledge and outline future perspectives for important pathologies like necrotizing enterocolitis (NEC) of the newborn, short bowel syndrome (SBS) and Hirschsprung´s disease associated enterocolitis (HAEC). Only studies applying next generation sequencing techniques to analyse the diversity of the intestinal microbiome were included. In NEC patients intestinal dysbiosis could already be detected prior to any clinical evidence of the disease resulting in a reduction of the bacterial diversity. In SBS patients the diversity seems to be reduced compared to controls. In children with Hirschsprung´s disease the intestinal microbiome differs between those with and without episodes of enterocolitis. One common finding for all three diseases seems to be an overabundance of Proteobacteria. However, most human studies are based on fecal samples and experimental data question whether fecal samples actually represent the microbiome at the site of the diseased bowel and whether the luminal (transient) microbiome compares to the mucosal (resident) microbiome. In conclusion current studies already allow a preliminary understanding of the potential role of the intestinal microbiome in pediatric surgical diseases. Future investigations could clarify the interface between the intestinal epithelium, its immunological competence and mucosal microbiome. Advances in this field may have an impact on the understanding and non-operative treatment of such diseases in infancy.